La Shoah à Salonique dans l’œuvre de l’écrivain Georges Ioannou - Loïc Marcou (Cahiers Balkaniques)
Salonika is the Greek town that suffered the most from the Holocaust. Called “the Balkans Jerusalem” for a long time, the historical main town of Greek Macedonia is almost “judenrein” at the end of the German occupation. In the work of George Ioannou (1927-1985), one of the most important prose writer of Post-War Greece, the Holocaust has a special place because the author is haunted by ghosts from the past. In the following pages, the reader will discover two of the seven texts written by Ioannou, as witness, from his own experience of the Holocaust in Salonika.